APPLICATION OF PAI LEARNING METHODS TOWARDS UNDERSTANDING OF RELIGIOUS CONCEPTS HOW TO PRACTICE THE FIVE TIMELY PRAYERS IN THE DAILY LIFE OF STUDENTS OF STATE ELEMENTARY SCHOOL 056649 B HITAM - Siregar, Tuti Sriwahyuni; Hasanah, Siti; Safitri, Zainal; Mahmudah; Soraya, Fitri (Journal of Quality Islamic Education Research, 2025)
This study aims to analyze the application of Islamic Religious Education (PAI) learning methods in improving students' understanding of religious concepts, especially how to practice the five daily prayers in everyday life at SD Negeri 056649 B Hitam. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation studies. The results of the study indicate that the application of appropriate learning methods, such as lectures, discussions, and direct practice, can improve students' understanding of the procedures for implementing the five daily prayers. In addition, learning that involves active student participation has also proven effective in internalizing religious teachings and applying them in everyday life. Methods that are contextual and relevant to students' conditions are expected to strengthen a deep understanding of religion, especially in carrying out prayer. This study suggests the importance of developing more interactive PAI learning methods that are in accordance with students' needs so that they can understand and implement the five daily prayers well and consistently in their lives. Thus, PAI learning can contribute significantly to the formation of students' character and spiritual depth.